Editorial: Special issue on embodied making and learning - Groth, Camilla; Riis, Kirstine; Sørebø Gulliksen , Marte (FormAkademisk, 2020)
This special issue on embodied making and learning is dedicated to aspects of embodied cognition that goes on in the field of art, craft and design. The contributors to this issue were invited from the Embodied Making and Learning (EMAL) research group at the University of South-Eastern Norway, where aspects of learning in creative practices have been studied from many different angles throughout the institutions nearly 80 years existence, and amplified since the formation of the group in 2014. With its 50 members, divided into five thematic clusters related to embodied making and learning, this research group is one of the largest in the field. It involves both experienced and early career researchers, as well as experienced university teachers, from several disciplines.